Peran Motivasi Dalam Meningkatkan Kinerja Pegawai Pada Dinas Pendidikan Kabupaten Merauke - Lila Santi; Rumlus, Herman CMS (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2025)
Motivation is what causes, channels, and supports human behavior so that they want to work hard and enthusiastically to achieve optimal results. This study aims to analyze the role of work motivation in improving employee performance in Merauke Regency Education Office. Work motivation is believed to have a significant impact on the level of productivity, quality of work, and overall efficiency. This research uses a descriptive qualitative approach. Data was collected through observation, interviews, and documentation. The results of the study found that work motivation in Merauke Regency Education Office plays a very important role in supporting the existing work. Maximum work motivation will result in maximum employee performance. Supporting factors for improving performance include the intention of employees who want to develop themselves, the competitiveness of employees to develop. leaders can provide motivation to employees who excel will be given an award, as well as attention from leaders. In addition, inhibiting factors include unfulfilled employee rights, lack of creativity and employee concern about duties and responsibilities, employee indifference, and lack of supporting facilities.